2011
DOI: 10.1016/j.aquaculture.2011.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of different wheat products in white shrimp Litopenaeus vannamei juveniles

Abstract: Dry matter, energy, crude protein and amino acid apparent digestibility coefficients (ADCs) were determined in white shrimp juveniles for six wheat products: hard red winter whole grain meal (HWG), Rayon whole grain meal (RWG), Durum whole grain meal (DWG), hard red winter clear flour (HCF), mixed wheat 2nd clear flour (MCF) and semolina (S). The test diets included 30% of the test ingredients and 70% of a ground commercial diet supplemented with 1% chromic oxide and 1% sodium alginate. Amino acid contents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…; Nieto‐López et al . ), information on digestibility coefficients for novel feed ingredients is indispensable to allow for accuracy in dietary formulations as these ingredients become commercially available. Among the common ingredients that have been investigated as fishmeal replacements, soybean meal has generally been successfully incorporated into shrimp formulations (Lawrence et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Nieto‐López et al . ), information on digestibility coefficients for novel feed ingredients is indispensable to allow for accuracy in dietary formulations as these ingredients become commercially available. Among the common ingredients that have been investigated as fishmeal replacements, soybean meal has generally been successfully incorporated into shrimp formulations (Lawrence et al .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of linear regression showed that the ADC between total amino acids and protein was highly correlated for fungal fermented plant proteins in P. indicus (r = 0.8229) compared to P. monodon ( r = 0.7447). Similar results were reported in P. vannamei fed different wheat products (Nieto‐López et al, ). In this study, protein had a higher digestibility than total amino acids in P. monodon (0.69%–2.71%) and the increase was in the range of 0.32%–2.75% in P. indicus.…”
Section: Discussionmentioning
confidence: 97%
“…However, a higher correlation between the ADC of total amino acids and protein ( r = 0.99) was observed in soy products (Cruz‐Suárez et al, ). This confirmed that the total amino acids to protein varied for differently processed samples and corroborates the findings of Nieto‐Lopez et al ().…”
Section: Discussionmentioning
confidence: 99%
“…The amino acids that had the highest leaching rates were lysine (21%), methionine (15%), and histidine (12%) (see table 4). The amino acid ADC adjusted for losses due to leaching also varied in relation to the ingredient used to prepare the diet (table 5): the poultry meals had the highest concentrations (poultry meal 1, perdidos en el agua por efecto de lixiviación (Nieto-López et al 2011).…”
Section: Amino Acid Losses and Apparent Digestibility Coefficients Comentioning
confidence: 99%
“…The ADC of the test ingredients were calculated according to Bureau and Hua (2006). The ADC of the diets and ingredients were adjusted considering the percent of nutrient loss in seawater due to leaching (Nieto-López et al 2011).…”
Section: Calculation Of Digestibility Coefficientsmentioning
confidence: 99%